Survey of insect pests of stored grain in New Zealand - Chapman, R.B.; Marris, J.W.M.; Drummond, J.B. (New Zealand Plant Protection, 2016)
Producers and processors of cereal grains in New Zealand were invited in August 2015 to submit grain samples to allow extraction and identification of any insect pest species present Sixty grain samples were received of which 73 were infested with one or more insect species These were predominantly Coleoptera and Psocoptera The most frequently encountered beetle species were Oryzaephilus surinamensis Cryptolestes ferrugineus and Cortinicara hirtalis The Psocoptera were predominantly unidentified species of Liposcelis Sitophilus species and lepidopteran pests were notable by their absence The proportion of storage facilities infested by insects in this survey (73) was higher than two previous surveys (38 5063) and the proportion of storage facilities treated with insecticides (62) was lower than a previous survey (83)